ANALISIS PENGUKURAN MINAT PENGGUNA APLIKASI PAYTREN DALAM PENGGUNAAN MOBILE PAYMENT DI ACEH - Evayani Evayani; Dini Ariani; Dinaroe Dinaroe (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2021)
In recent years, the number of internet users and smartphones was increasing enormously in Indonesia. The development of the internet occurs rapidly and gives a significant influence on every aspect of life. The growing information technology allows people to easily perform various financial transactions by using mobile payments. This research aimed to examine the influence of mobility, compatibility, and trust toward the intention of users to use mobile payment. The research was conducted in Banda Aceh by taking samples of the PayTren users. The purposive sampling method was being used in gathering data and the main instrument of data collection was in the form of a questionnaire, which was being measured on a Likert scale. The data Samples were Banda Aceh inhabitants who use PayTren as their mobile payment platform. A total of 119 data were processed using SPSS and the analysis result of the model showed that mobility, compatibility, and trust affected the intention to use mobile payment PayTren.